2012
DOI: 10.3389/fphys.2012.00215
|View full text |Cite
|
Sign up to set email alerts
|

Somatosympathetic Vasoconstrictor Reflexes in Human Spinal Cord Injury: Responses to Innocuous and Noxious Sensory Stimulation below Lesion

Abstract: It is known that the sudden increases in blood pressure associated with autonomic dysreflexia in people with spinal cord injury (SCI) are due to a spinally mediated reflex activation of sympathetic vasoconstrictor neurons supplying skeletal muscle and the gut. Apart from visceral inputs, such as those originating from a distended bladder, there is a prevailing opinion that autonomic dysreflexia can be triggered by noxious stimulation below the lesion. However, do noxious inputs really cause an increase in bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
(95 reference statements)
1
4
0
Order By: Relevance
“…Visceral stimulation in decerebrate animals led to increases in RSNA and MAP, which were accompanied by decreases in HR. This pattern is similar to what is reported in human subjects (3,4,25,30). Reflex reactivity is attenuated by the administration of anesthesia and abolished by ganglionic blockade.…”
Section: Viscero-sympathetic Reflex Reactivity In Decerebrate Animalssupporting
confidence: 89%
“…Visceral stimulation in decerebrate animals led to increases in RSNA and MAP, which were accompanied by decreases in HR. This pattern is similar to what is reported in human subjects (3,4,25,30). Reflex reactivity is attenuated by the administration of anesthesia and abolished by ganglionic blockade.…”
Section: Viscero-sympathetic Reflex Reactivity In Decerebrate Animalssupporting
confidence: 89%
“…Our main findings were as follows: (i) in all 16 patients with spinal lesions above the level of sympathetic outflow to the hand, bladder filling induced signs of cutaneous vasoconstriction in the fingers; (ii) in 10 of those patients the blood pressure increased by 10 mmHg or more, and in nine of them there was a significant inverse relationship between finger pulse amplitudes and mean blood pressure; and (iii) there was no evidence of sweat release throughout the procedure in any patient, supporting our contention that sweat release is not a reliable marker of cutaneous sympathetic outflow below the lesion in human spinal cord injury (Brown et al 2007, 2009 a , b ; Macefield et al 2012).…”
Section: Discussionmentioning
confidence: 64%
“…In addition, a variety of stimuli applied below the lesion may lead to sudden increases of blood pressure (autonomic dysreflexia), sometimes to alarmingly high levels (Erickson, 1980; Teasell et al 2000). Most commonly the stimuli originate from the viscera, but non‐noxious sensory inputs from the body wall may occasionally evoke strong somatosympathetic reflexes below the lesion (Macefield et al 2012). Stimuli applied to the urinary bladder are especially effective at evoking marked increases in blood pressure, and several studies have reported a high incidence of autonomic dysreflexia during cystoscopy (Snow et al 1978) or cystometry (Guttman & Whitteridge, 1947; Krum et al 1992; Curt et al 1997; Giannantoni et al 1998; Lee et al 2003).…”
mentioning
confidence: 99%
“…If the spinal cord injury is located above the level of the cardiac sympathetic output (i.e., higher cervical injuries), the reflex-mediated bradycardia is absent and a tachycardiac response is observed (Eldahan and Rabchevsky, 2018). Similar cardiovascular responses can be produced by cutaneous stimulation below the level of the spinal cord injury through activation of a somato-sympathetic reflex (Brown et al, 2007(Brown et al, , 2009Macefield et al, 2012). In addition to cardiovascular responses, activation of viscero-sympathetic reflex can result in throbbing headache, nausea, irritability, and sometimes even convulsion, cerebral hemorrhage or death (Eldahan and Rabchevsky, 2018).…”
Section: Viscero-sympathetic Reflexes In Humansmentioning
confidence: 99%